ETHICAL AND ECOLOGICAL PERSONAL UP-BRINGING BY MEANS OF LITERARY WORDS THROUGH THE AUTHOR’S CONCEPT OF VASYL SUKHOMLYNSKYI - Bilavych, Halyna; Ozarko, Veronika; Khanas, Oleksandra; Litvin, Yulia (Mountain School of Ukrainian Carpaty, 2022)
The aim of the study is to analyze the author's system of ethical and ecological education of the personality of Vasyl Sukhomlynskyi, to characterize the creative heritage of the scientist, to single out literary works for children with a moral and ecological content. Leading in the pedagogical legacy, in particular the literary work, of the outstanding Ukrainian scientist V. Sukhomlynskyi is the problem of moral education, which was the author's pedagogical system and found a practical embodiment in the Pavlysh secondary school, which the innovative teacher headed for almost thirty years. The conceptual provisions of the author's system of moral education of V. Sukhomlynskyi about the unity of moral education and nature conservation are important, especially nowadays, when the preservation of the Carpathian Mountains is gaining national importance, and the problems of ecological education of the individual are becoming an important condition for sustainable development in its global dimension. This problem sounds in a new way under the conditions of Russia's invasion of the territory of Ukraine on February 24, 2022, which caused the destruction of ecosystems, natural resources, chemical pollution of territories, waters, etc. Therefore, the problem of ecological education of children and youth is becoming actualized, they should become active ecologists-saviors of native nature and the environment, accordingly, teachers should develop a set of environmental measures of nature conservation content, develop a new philosophy of the formation of ecological culture of the individual throughout life, give ecological education of the individual a new sound, in particular practice oriented direction. It is proven that in this process it is possible to use the creative achievements of V. Sukhomlynskyi, whose literary works for children are an effective means of forming ethical and ecological education of children and adults. Each fairy tale or story with an environmental content offers the reader an invaluable moral lesson. These works are a moral code, a table book that you need to read every day in order to build your relationship with nature properly, to protect it, to take care of all living things, they are a kind of pedagogical commandments on how to be a person and, under today's conditions, to grow into an effective environmentalist in order to preserve not only nature, but also Ukraine. Keywords: V. Sukhomlynskyi, author's system, teacher-innovator, ethical and ecological education, literary works for children, ecological education, New Ukrainian school.